Knowledge of green computing among university students and lecturers in a Malaysian public university - Bello, Abdullahi; Tunku Ahmad, Tunku Badariah; Nordin, Mohamad Sahari (Global Science and Technology Forum (GSTF), 2013)
This study examined the levels of green computing knowledge between students and lecturers, and between ICT and non-ICT respondents in a public university in Malaysia. Two types of green computing knowledge were assessed, perceived knowledge and objective knowledge. Perceived knowledge was assessed through respondents’ self-rating of how much they knew about green computing on eight Likert items, and objective knowledge through seventeen True-False items. The sample consisted of 240 respondents, comprising 180 students and 60 lecturers, drawn using a purposive, random sampling. Data were collected using a self-developed green computing questionnaire, which was administered by hand and via e-mail. Descriptive statistics and independent-samples t-tests were used to analyze the data. Results show that almost half of the sample reported having completely no knowledge of green computing (49.5%), while 14.6% reported having a low level of knowledge. Those reporting having high (2.6%) and quite high (9.7%) levels were few in number. Results of the t-tests point to a no-significance difference between students and lecturers, but a statistically significant difference between ICT and non-ICT respondents. The findings suggest the importance of conscious training in energy-efficient computing to raise students’ and lecturers’ levels of knowledge in this very important area.